2021
DOI: 10.1073/pnas.2101416118
|View full text |Cite
|
Sign up to set email alerts
|

CRY2 missense mutations suppress P53 and enhance cell growth

Abstract: Disruption of circadian rhythms increases the risk of several types of cancer. Mammalian cryptochromes (CRY1 and CRY2) are circadian transcriptional repressors that are related to DNA-repair enzymes. While CRYs lack DNA-repair activity, they modulate the transcriptional response to DNA damage, and CRY2 can promote SKP1 cullin 1–F-box (SCF)FBXL3-mediated ubiquitination of c-MYC and other targets. Here, we characterize five mutations in CRY2 observed in human cancers in The Cancer Genome Atlas. We demonstrate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…However, CRY2 up-regulation is described in chemoresistant colorectal cancer patients [ 120 ]. In addition, Chan et al [ 121 ] showed that mutations in CRY2 led to p53 suppression and provided cell proliferation. Thus, the different expression levels of CRY1 and CRY2 appear to impact leukemic cells over different pathways, showing the need for further investigation into these mechanisms in order to elucidate their value as a leukemic biomarker [ 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CRY2 up-regulation is described in chemoresistant colorectal cancer patients [ 120 ]. In addition, Chan et al [ 121 ] showed that mutations in CRY2 led to p53 suppression and provided cell proliferation. Thus, the different expression levels of CRY1 and CRY2 appear to impact leukemic cells over different pathways, showing the need for further investigation into these mechanisms in order to elucidate their value as a leukemic biomarker [ 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Apc locus is a known target of point mutations, insertions, deletions, and LOH events, which have been described to drive tumor progression (14,63). In addition, the circadian clock is reported to be involved in the DNA damage response and DNA repair (39,(64)(65)(66)(67). Disruption of the clock may therefore accelerate mutagenic burden.…”
Section: Bmal1 Disruption Accelerates Apc Lohmentioning
confidence: 99%
“…The circadian clock maintains cellular homeostasis and systemic physiology (31)(32)(33). However, altered circadian gene expression signatures are associated with several diseases including multiple cancer types (34)(35)(36)(37)(38)(39)(40)(41)(42). Human data from The Cancer Genome Atlas (TCGA) show a significant correlation between a subset of deregulated core clock genes and oncogenic driver pathways, survival rates, and tumor staging in 32 different cancer types (43).…”
Section: Introductionmentioning
confidence: 99%
“…KS15 has anti-proliferative effects on breast cancer MCF-7 cells by increasing p53 and Bax gene expression (Chun et al, 2015). Considering that CRY1 and CRY2 have been associated with p53 suppression or degradation in other cancers (Chan et al, 2021;Jia et al, 2021) and that Cry1 and Cry2 knockout in p53 mutant mice reduces cancer risk (Ozturk et al, 2009), KS15, or its derivatives (Jeong et al, 2021) may be efficacious in the treatment of several cancers, in addition to MCF-7 breast cancer. Together, these results identified CRYs as promising targets of small-molecule compounds.…”
Section: Identification Of Cry-targeting Compoundsmentioning
confidence: 99%
“…CRY dysfunction has been implicated in diseases, such as circadian sleep disorders (Hirano et al, 2016;Patke et al, 2017) and diabetes (Zhang et al, 2010;Lamia et al, 2011). Furthermore, CRY1 and CRY2 isoforms have been differentially associated with cancer and may function as pro-or antitumorigenic factors depending on the type of cancer (Chan and Lamia, 2020;Chan et al, 2021;Shafi et al, 2021). CRYs therefore represent attractive drug targets for the treatment of CRY-mediated and circadian clock-related diseases.…”
Section: Introductionmentioning
confidence: 99%